Erratum: View factors between disk/rectangle and rectangle in parallel and perpendicular planes (Journal of Thermophysics and Heat Transfer (2007) 21:1 (236-239)) - Sridhar, Abishek; Ramanujam, K.; Katte, S. (American Institute of Aeronautics and Astronautics, Inc., 2014)
Typographical errors in the equations in the paper